Cellular Prion Protein as a Receptor of Toxic Amyloid-β42 Oligomers Is Important for Alzheimer’s Disease - Zhang, Yuan; Zhao, Yanfang; Zhang, Lei; Yu, Wanpeng; Wang, Yu; Chang, Wenguang (Frontiers in Cellular Neuroscience, 2019)
The pathological features of Alzheimer’s disease (AD) include senile plaques induced by amyloid-β (Aβ) protein deposits, neurofibrillary tangles formed by aggregates of hyperphosphorylated tau proteins and neuronal cell loss in specific position within the brain. Recent observations have suggested the possibility of an association between AD and cellular prion protein (PrPC) levels. PrPC is a high affinity receptor for oligomeric Aβ and is important for Aβ-induced neurotoxicity and thus plays a critical role in AD pathogenesis. The determination of the relationship between PrPC and AD and the characterization of PrPC binding to Aβ will facilitate the development of novel therapies for AD.